The Study of the Mission and Responsibility of Drawing Major in Local Universities from the Aspect of the “Double First-Class” - Yongsong Shi, Zihan Liu, Wenxuan Ma (Forest Chemicals Review, 2022)
The “Double First-Class” initiative, the important move of elevating the national education’s international competitiveness, is the solid base of realizing the great rejuvenation of the Chinese Nation and adhering to the cultural confidence. Based on the characteristic of normal university, the drawing major of Hanjiang Normal University has taken the responsibility for celebrating and developing the local culture. On the basis of the study about the Wudang and Hanshui culture, the major strives to cultivate the teacher of basic education and educate the application-oriented undergraduate who will develop and celebrate the local culture, starting by developing the characteristic course. It endeavors to become the regionally “First-Class” major, and to promote the development of local economy and culture.